2018
DOI: 10.1097/dad.0000000000001042
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin Profile of Basal Cell Carcinomas According to the Degree of Sun Exposure and to the Anatomical Localization

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…As we mentioned earlier, although BCC is essentially located on sun-exposed skin, vulvar BCC is located on a nonexposed site. CK7 expression seemed to be associated with non–sun-exposed areas 8. Studies showed that positive CK7 and CK19 stain could suggest a glandular origin considering this genital region rich in sebaceous and apocrine units 9.…”
Section: Discussionmentioning
confidence: 95%
“…As we mentioned earlier, although BCC is essentially located on sun-exposed skin, vulvar BCC is located on a nonexposed site. CK7 expression seemed to be associated with non–sun-exposed areas 8. Studies showed that positive CK7 and CK19 stain could suggest a glandular origin considering this genital region rich in sebaceous and apocrine units 9.…”
Section: Discussionmentioning
confidence: 95%
“…However, some authors have observed, 4 such as this study, CK7 expression showed differences depending on the BCC localization. In a study of García-de-la-Fuente et al (2018) 4 the percentages of CK7-positive cases located on the face, the trunk, and the non-sun exposed parts of the body (such as vulva, axilla, perineum) were 53. 3, 81.8, and 100%, respectively. Obviously, there was the lowest proportion of the CK7-positive BCCs located on the skin permanently exposed to sunlight.…”
Section: Discussionmentioning
confidence: 98%
“…In this case, CK7 also showed low positive expression in the scalp lesions. 22 Studies have shown that AR is expressed in many skin tumors, with about 50–60% of BCC cases expressing AR. In contrast, AR is barely expressed in mature hair follicle, epidermal, or benign hair follicle tumors such as TE.…”
Section: Discussionmentioning
confidence: 99%